Redesain Struktur Bawah Pada Rumah Tinggal Akibat dari Penurunan Bangunan (Studi Kasus) - Diana Ningrum; Galih Damar Pandulu (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
Residential house in Perumahan Gadang Regency Blok P2 no. 33 Malang was built in 2005. Over time the building experienced consolidation, that it suffered structural and architectural damage. Therefore, it is necessary to redesign the substructure (foundation). All planned construction will be supported by the ground. Passing on the load of the structure above the ground, other forces acting on the supporting ground of the building is the main function of the building structure which is usually called the foundation. The CPT results are presented in the form of a sonder diagram which records the value of CONUS resistance and sheath friction, then used to calculate the bearing capacity of the foundation placed on the soil. Data were obtained at the test point where the depth of the sonder test was stopped at a depth of 6.00 m. So that in the redesign of the lower structure of the residence it was determined using the type of deep foundation, a Strauss foundation was selected with a depth of 4.1 m and a foot foundation of 1.9 m. Based on the loading data and analysis with STAADPro software, it is planned that the dimensions of the Strauss diameter are 20 cm, the concrete cover is 5 cm and the number of reinforcement is 8, the diameter of the reinforcement is âˆ…12 and the stirrup is 12-150, h = 4.1m and the foundation dimensions are 80x80x30, reinforcing D13-150.